PMO-138 The molecular mechanisms of B cell and B cell lymphoma recruitment to the human liver. (28th May 2012) - Shetty, S; Bruns, T; Weston, C; Stamataki, Z; Oo, Y; Hubscher, S; Jalkanen, S; Lalor, P; Adams, D H
Abstract : Introduction: There is gathering interest in the presence of B cells within liver tissue and their contribution to chronic inflammation and fibrosis but the recruitment signals for B cells into peripheral tissue is poorly understood. In addition a large proportion of lymphomas which infiltrate the liver are of B cell origin but again little is understood of the mechanism that underlies this process. Lymphocyte recruitment to the liver occurs within the hepatic sinusoidal channels. These low shear vascular beds are lined by specialised hepatic sinusoidal endothelial cells (HSEC). Our aim was to understand the molecular mechanisms of B cell and B cell lymphoma recruitment to the liver. Methods: We used isolated human HSEC in flow assays with purified peripheral blood B cells to elucidate the molecular mechanisms of B cell recruitment via HSEC. The contribution of conventional adhesion molecules, ICAM-1 and VCAM-1 and unconventional molecules VAP-1 and CLEVER-1/stabilin-1 was assessed by using function blocking antibodies. We repeated our experiments with two B cell lymphoma cell lines, CRL-2261 and Karpas B cell line. We assessed the contribution of chemokines by performing transwell assays and adding chemokines to our flow assays. We also tracked the motility of B cells and lymphoma cell lines on HSEC using tracking software. Results: B cells were captured from flow and firmly adhered to HSEC, the primary adhesion receptor on HSEC was VCAM-1. B cells also underwent transendothelial migration which was mediated by a combination of ICAM-1, VAP-1 and CLEVER-1/stabilin-1. Lymphoma cell line recruitment shared several features of primary lymphocyte homing, firm adhesion was mediated by ICAM-1 and VCAM-1 and they demonstrated shape-change and crawling behaviour which was ICAM-1 dependent. The lymphoma cell lines did not undergo transendothelial migration and this could not be initiated with the addition of SDF-1α. Conclusion: There is increasing evidence that B cells play an important role in chronic inflammatory liver diseases. The recruitment signals we have identified for B cells in this study may provide potential therapeutic targets for liver disease. Furthermore we have demonstrated preserved lymphocyte homing mechanisms in malignantly transformed B cells. These properties could be therapeutic targets to prevent lymphoma dissemination to the liver. Competing interests: None declared.